Analisis Tipologi Berdasarkan Indikator Fundamental Ekonomi Daerah - Vivi Ukhwatul Masbiran (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2019)
Equitable economic growth and the quality of human resources are one of the targets in the medium-term planning documents of Sumatera Barat Province. The determination of the areas that are the development priorities for achieving macro performance indicators is very important in the government sector. This study aims to identify the typology of districts / cities in Sumatera Barat during the period of 2010-2018 as an evaluation of the government in determining the priority areas of development to achieve equity. The research method used is a quantitative method with descriptive analysis. Sources of data obtained from BPS of Sumatera Barat Province. Data were analyzed using Klassen's typology, which divides four quadrants based on fundamental indicators namely economic and welfare indicators. The results of typology analysis based on economic indicators show that there are 7 (seven) districts in the Developing Regions quadrant, 5 (five) districts in the Advanced Regional quadrant, 4 (four) districts in the Developed but Depressed Regional quadrant, and 3 (three) districts in Fast Developing Regional quadrant. Based on welfare indicators, regions that have high per capita income and HDI are City Administrative Regions, while regions with low per capita income and HDI are dominated by Regency. Abstrak Pemerataan pertumbuhan ekonomi dan kualitas sumber daya manusia menjadi salah satu sasaran dalam dokumen perencanaan jangka menengah daerah Provinsi Sumatera Barat. Penentuan daerah yang menjadi prioritas pembangunan untuk pencapaian indikator kinerja makronya merupakan hal yang sangat penting dalam sektor pemerintahan. Penelitian ini bertujuan untuk mengidentifikasi tipologi Kabupaten/Kota di Sumatera Barat selama periode 2010-2018 sebagai bahan evaluasi pemerintah dalam menentukan daerah prioritas pembangunan untuk mewujudkan pemerataan. Metode penelitian yang digunakan adalah metode kuantitatif dengan analisis deskriptif. Sumber data didapatkan dari BPS Provinsi Sumatera Barat. Data dianalisis dengan menggunakan tipologi Klassen, yaitu pembagian 4 (empat) empat kuadran berdasarkan indikator fundamental: ekonomi dan kesejahteraan. Hasil analisis tipologi berdasarkan indikator ekonomi menunjukkan ada 7 (tujuh) kabupaten pada kuadran Daerah Tertinggal, 5 (lima) kabupaten pada kuadran Daerah Maju, 4 (empat) kabupaten pada kuadran Daerah Maju Tapi Tertekan, dan 3 (tiga) kabupaten pada kuadran Daerah Berkembang Cepat. Berdasarkan indikator kesejahteraan, daerah yang memiliki pendapatan per kapita dan IPM tinggi adalah daerah administratif Kota, sedangkan daerah dengan pendapatan per kapita dan IPM rendah didominasi oleh daerah kabupaten.